The relationship between living arrangements and depression among older adults in Shandong, China: The mediating role of social support - Pei, Zhongfei; Hu, Fangfang; Qin, Wenzhe; Zhao, Yan; Zhang, Xiaohong; Cong, Xinxia; Liu, Chuanli; Xu, Lingzhong (Frontiers in Psychiatry, 2022)
Abstract:(1) Background: Living arrangements and social support have an impact on depression among older adults. However, the underlying mechanism between those variables remains unknown. This study aims to investigate the mediating role of social support in the relationship between living arrangements and depression among older adults. (2) Methods: Multi-stage stratified sampling method was used to select 3859 older adults from Taian City, Shandong Province, China, for cross-sectional investigation. Living arrangements were measured by a question. Social support and depression were measured using the Multidimensional Scale of Perceived Social Support and Patient Health Questionnaire-9. Multiple linear regression models were used to assess the relationship between living arrangements and depression and the possible influence of social support on the relationship between living arrangements and depression. (3) Results: Statistics showed that 15.1% of the older adults lived alone, and the overall prevalence of depression in subjects was 25.03%. After controlling for covariates, living arrangements (β=0.45, t=2.87, P<0.01) and social support (β=-0.08, t=-16.93, P<0.001) were significantly associated with depression. The linear regression model showed that social support mediated the relationship between living arrangements and depression, and the mediating effect accounted for 18.20% of the total effect. (4) Conclusions: This study revealed that living arrangements played an essential role in indirectly predicting depression in older adults through social support. This provided evidence for how to reduce depression in older adults.